Prosodic vowel lengthening in a spontaneous speech corpus of Vimeu Picard - Halicki, Eric (Lingua Posnaniensis, 2016)
The goal of this paper is to present findings about vowel lengthening at morpho-syntactically defined prosodic boundaries. The data come from a corpus of spontaneous speech from Vimeu Picard, a Gallo- Romance language. A total of 10 672 vowel durations are measured, and 5336 vowel ratios are calculated, providing data for the prosodic word, clitic group, phonological phrase, intonational phrase, and the utterance. A general increase in vowel duration is observed as one ascends the prosodic hierarchy, without adjusting for rate of speech. Significant differences in vowel ratio are found between the clitic group and all other phrases, the prosodic word and the intonational phrase, the phonological phrase and the intonational phrase, and the intonational phrase and the utterance. Contrary to what was expected, vowel ratios at the utterance edge were found to be significantly shorter than vowel ratios at the intonational phrase edge. This may be because pauses are greater for the utterance than for the intonational phrase.